Implementing environmental practices within the Greek dairy supply chain: Drivers and barriers for SMEs - Ghadge, Abhijeet; Kaklamanou, Merilena; Choudhary, Sonal; Bourlakis, Michael (Emerald, 2017)
Purpose: Food supply chain in Greece is dominated by SMEs, who face several challenges in adopting green practices. This research attempts to identify the key drivers and barriers influencing the environmental performance of SMEs within the Greek dairy supply chain. Design/methodology/approach: Descriptive research methodology attempts to prioritize the drivers and barriers for improving the environmental sustainability performance. Analytical hierarchy process and sensitivity analysis are used to understand the complex nature of the influencing factors. Findings: The analysis identify five barriers and six drivers for the implementation of green practices within the dairy supply chain. While external drivers significantly influence the market structure and logistics network; Government, competitors and customers are the driving factors for improving environmental performance. Research implications: The study contributes to filling the literature gap on key factors influencing the implementation of green practices within the food supply chain. The identified influential factors will contribute towards building a framework for improving sustainability performance within the Greek dairy supply chain. Practical implications: The study is expected to benefit the Greek and European SMEs by driving their environmental practices within the perishable supply chain network. Originality/value: The paper provides directions for researchers, practitioners and policy makers in understanding the challenges for implementing green practices in the dairy supply chain. The holistic approach followed in this paper is a building block for a conceptual framework on implementing environmental sustainability within the food supply chain. Apart from contributing to the current literature by extending the research horizon to SMEs’ green adoption capability, this study also provides better understanding of the pivotal role of internal and external key factors in influencing sustainability performance.
Keywords: Food supply chain; Environmental performance; SMEs; Greek dairy sector; Barriers and drivers